Identification of 3'-terminal exons from yeast artificial chromosomes. - Krizman, D B; Hofmann, T A; DeSilva, U; Green, E D; Meltzer, P S; Trent, J M (Genome Research, 1995)
We report an extension of 3'-terminal exon trapping technology to the identification of transcribed sequences from yeast artificial chromosomes (YACs). A 350-kb YAC containing mouse genomic DNA was gel-purified and used as the target DNA for the 3'-terminal exon trapping strategy. A novel direct ligation/transfection approach was employed to increase the efficiency of trapping 3'-terminal exons from recombinant vector-derived chimeric mRNA. The resulting RT-PCR product was then used to generate a plasmid library. Randomly chosen individual subclones from this library were sequenced, and the results indicate that 86% met sequence criteria characteristic of 3'-terminal exons, whereas 14% were background from identified sources. PCR mapping efforts suggest eight putative last exons present within this YAC, whereas RT-PCR studies demonstrate that three reside within valid expressed sequences.